Epidemiological characterization and prevalence of schistosomiasis in State of Maranhão, Brazil (Research, Society and Development, 2020)
The objective of the present work was to describe the biological and epidemiological characteristics of schistosomiasis in the years 2010 to 2016 Information System of the Schistosomiasis Control Program and 2010 2017 in the Information System for Notifiable Diseases in the state of Maranhão- BR. This is an epidemiological, retrospective and descriptive study of a population nature, using secondary data from cases of Schistosomiasis in Maranhão, evaluating aspects related to patient sex, species of snails, clinical evolution, geo-helminths associated with the disease, eggs parasites, number of tests performed and positive diagnoses, and finally cases confirmed by micro-region of residence according to the IBGE. The data were tabulated using the TABNET and Microsoft Office Excel 2019 programs. 333 cases of treatment for Schistosomiasis were observed. Of these, it was found that the male gender was the most frequent in the patients, corresponding to 245 (73.6%) and 52.0% of notified cases were of the species Biomphalaria straminea and 47.1% of Biomphalaria glabrata. cure clinic showed 78.6% (n = 262). The geo-helminthes most associated with schistosomiasis were Ascaris lumbricoids (n = 81,082; 42.1%) and Hookworms (n = 81,154; 42.1%). According to the number of eggs in the exam, it was observed that the notifications were greater than 1 to 4 eggs (72.9%). It was also analyzed that the total number of tests corresponded to 534,679, of this 19999 positive diagnoses. The cases confirmed by Microregion IBGE of residence had a higher incidence in Gurupi, with 192 of the cases.